Why Do Poor People Co-Hold Debt and Liquid Savings?. Issue 2 (1st February 2018) - Laureti, Carolina
Abstract: I examine the use of flexible savings-and-loan accounts offered by SafeSave, a microfinance institution serving poor slum dwellers in Dhaka, Bangladesh. I find that 59 per cent of the clients co-hold, meaning that they borrow at high interest rates and simultaneously hold low-yield liquid savings. Co-holders could immediately pay down, on average, 32 per cent of their debt using liquid savings and thus avoid significant interest payments. The results show that co-holders are more likely to be regular workers subject to little income uncertainty, suggesting that co-holding is not a consequence of liquidity needs. The paper discusses alternative explanations.